Desain Sistem Raport Online SMP Berbasis Website ASP.NET C# Dengan Pendekatan Konsep MVC - mardiana andarwati; Bima Sakti Putra; Kukuh Yudhistira (LPPM STIKI MALANG, 2019)
The development of IT in over time was very important for every circle, from individual person until for organization. Furthermore, to make the function of IT more optimalized in education system, the writer did the research about the using of raport online application base on website which was responsive with gadget to make easily the students and the foster parents monitored the students score without came into the school. Beside that, the teacher and the employee’s school will be help on collected the students score without used of computer or laptop. There were two research question to be investigated on this study, how is the system design of the raport online base on website which used on SMPN 2 Tanjunganom? Then, how is the result of the raport online base on website in SMPN 2 Tanjunganom?. This study used of application with built on MVC ASP.NET method (Visual Studio 2014), C#, Sql Server 2014 and with free hosting. In the collecting the data, the writer used of observation and interview techniques. The result of this study showed that the using of raport online application in SMPN 2 Tanjunganom which was used C# method MVC ASP.NET can be concluded that the application was efficient because the application was facilitate for the teacher and employee’s school on collecting the students score. Beside that, the students and the foster parents can be easily to use the application to monitored the result of students score. The writer suggested to the school’s side to more optimalized the IT facility in the school, this condition was very important to confronted the globalisation era with the technology do evolve over time.